2020
DOI: 10.1002/qre.2633
|View full text |Cite
|
Sign up to set email alerts
|

A bi‐objective optimization approach for the maintenance planning of networked systems

Abstract: Networked systems, such as telecommunications, transportation, and power transmission, are critical for the economic development and social well-being of a society and are required to keep the prescribed demand continuously satisfied. Therefore, when planning maintenance actions for such a system, the adverse influence on its reliability caused by the unavailability of the components in the process of being maintained needs to be taken into account. To deal with this problem, we propose a new bi-objective opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…We aim at the last type of model, but the bulk of research literature has only been found in the two first types (with static traffic flow modeling). From the coarse models we have not found any applicable modeling inspiration apart from Li and Zhang (2020) which use different time scales for track works and link status. This is an idea that could be applied to our case for upgrade projects and traffic flow.…”
Section: Literature Overviewmentioning
confidence: 99%
“…We aim at the last type of model, but the bulk of research literature has only been found in the two first types (with static traffic flow modeling). From the coarse models we have not found any applicable modeling inspiration apart from Li and Zhang (2020) which use different time scales for track works and link status. This is an idea that could be applied to our case for upgrade projects and traffic flow.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Many studies chose an NHPP with a Weibull power law intensity function because of its flexibility in terms of describing all of the reliability patterns in the system life phase. 14,15 Along with deterioration of the system, the system can experience failure at any time and will begin to produce defective products at a certain level. In other words, the quality of the product (yield rate) is related to the deterioration of the system.…”
Section: Introductionmentioning
confidence: 99%
“…The deterioration of a system can be described using stochastic models. Many studies chose an NHPP with a Weibull power law intensity function because of its flexibility in terms of describing all of the reliability patterns in the system life phase 14,15 . Along with deterioration of the system, the system can experience failure at any time and will begin to produce defective products at a certain level.…”
Section: Introductionmentioning
confidence: 99%
“…These update strategies are expected to assist industries to obtain the right balance between increasing availability, reliability, profit and revenues and decreasing breakdowns and maintenance costs 10 . Moreover, intensive maintenance activities could enhance asset reliability while increasing maintenance costs 11 . Optimising the asset maintenance schedule to maximise reliability and minimise maintenance costs is an essential and important research interest for water industries.…”
Section: Introductionmentioning
confidence: 99%